La teoria critica di Umberto Eco: La critica dell’ideologia e la guerriglia semiologica (ENTHYMEMA, 2012)
Through the exams of key concepts and the use of concrete examples, this paper demonstrates the close relationship between analysis and criticism one can find in Umberto Eco’s 1970s production. In particular, this contribution focuses on two fundamental aspects of Eco’s work: the analysis of ideology and the practice of opposition - the so called semiologic guerrilla warfare - aimed to subvert the hierarchical relationship between sender and receiver based on the notion of consensus. Aim of this paper is to show that, within Eco’s oeuvre, semiotics is not only a descriptive theory but, rather, an active practice able to reveal, and at the same time to overturn, the ideological and persuasive mechanisms behind the use of signs.